2014
DOI: 10.1002/2014gl060306
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude −7 level earthquakes: A new lower limit of self‐similarity in seismic scaling relationships

Abstract: Microfractures occurring in a rock sample that are called acoustic emission (AE) events show some similar features to earthquakes. However, it remains to be shown whether or not AE equate to ultramicroearthquakes. In this study, we show the existence of magnitude À7 level earthquakes based on seismological analyses of AE source parameters. Advances in multichannel, broadband, high-speed continuous recording of AE under seismogenic pressure conditions has facilitated increasingly robust measurement. Source para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 43 publications
8
50
0
Order By: Relevance
“…Stress drops of small and large earthquakes have been investigated and have almost confirmed the selfsimilarity of earthquakes (e.g., Kanamori and Anderson 1975;Abercrombie 1995;Prieto et al 2004;Yamada et al 2007;Yoshimitsu et al 2014). This self-similarity is important in that we can treat stress drops of earthquakes as indicators of the difference between the shear strength and the dynamic stress level on the fault plane, independent of the earthquake size.…”
Section: Stress Drop and Its Mechanical Significancementioning
confidence: 80%
“…Stress drops of small and large earthquakes have been investigated and have almost confirmed the selfsimilarity of earthquakes (e.g., Kanamori and Anderson 1975;Abercrombie 1995;Prieto et al 2004;Yamada et al 2007;Yoshimitsu et al 2014). This self-similarity is important in that we can treat stress drops of earthquakes as indicators of the difference between the shear strength and the dynamic stress level on the fault plane, independent of the earthquake size.…”
Section: Stress Drop and Its Mechanical Significancementioning
confidence: 80%
“…Stress drops of small and large earthquakes have been estimated to investigate the self-similarity of earthquakes (e.g., Abercrombie 1995; Kanamori and Anderson 1975;Prieto et al 2004;Yamada et al 2007). Recently, Yoshimitsu et al (2014) investigated acoustic emission (AE) events of a rock fracture experiment under seismogenic pressure conditions and pointed out that the AE events with magnitudes down to −8 satisfied the proportionality between the seismic moment and the corner frequency to the third power, or the constant stress drop. Another aspect of the stress drop analysis is the spatiotemporal heterogeneity of stress and strength.…”
Section: Studies On Seismicity and Stress Dropmentioning
confidence: 99%
“…3). A disagreement with a scaling of Δσ ∝ M 0 −1/4 is also observed for microearthquakes recorded at the SAFOD Pilot Hole at Parkfield (Imanishi and Ellsworth 2006) and repeating acoustic emission events from laboratory experiments (Yoshimitsu et al 2014). …”
Section: Discussionmentioning
confidence: 93%
“…Many studies have reported that the static stress drop is almost constant for the scale from natural earthquakes to acoustic emission events (e.g., Hiramatsu et al 2002;Imanishi and Ellsworth 2006;Yoshimitsu et al 2014). On the other hand, a spatial or temporal fluctuation of the static stress drop has often been recognized as well because the heterogeneity of stress and strength on a ruptured fault determines the value of the static stress drop (e.g., Shearer 2007, 2009;Hardebeck and Aron 2009;Oth 2013;Uchide et al 2014).…”
Section: Introductionmentioning
confidence: 99%